Rural and non-rural differences in minutes spent in physical activity and sedentary behavior - Braun, Kyle J. (Kansas State University, 2018)
BACKGROUND: Rural Americans face significant barriers for meeting recommended physical activity guidelines (Trivedi et al., 2015). Although studies have demonstrated adults in rural communities participate in less physical activity than their urban counterparts (Martin et al., 2005; Reis et al., 2004), the differences in physical activity for children and adolescents are not so clear. The main goal of this study was to explore potential differences among school physical activity (SPA), outside of school time physical activity (OSTPA), and sedentary behavior (SB), among rural and non-rural fourth and fifth-grade students. It was hypothesized that rural schools participate in less physical activity and more sedentary behavior than non-rural schools. Additionally, factors such as student gender and school socio-economic status were considered. METHOD: Data from the Youth Activity Profile (YAP), collected as part of the NFL PLAY60 FITNESSGRAM Partnership, is utilized to assess physical activity. The YAP captures the three constructs of SPA, OSTPA, and SB with fifteen questions (five questions each). A two-level mixed-model using SAS Proc Mixed was used to test for significant differences among groups. RESULTS: An analysis of least square means resulted in the following. Rural schools of fifth-grade students reported significantly more minutes in SPA (MD=8.68, 95% CI=-17.38, 0.01) than non-rural schools of fifth-grade students. Fourth-grade girls reported significantly fewer minutes in SPA (MD=11.1, 95% CI=9.09, 13.11), OSTPA (MD=19.55, 95% CI=17.54, 21.57), and more minutes in SB (MD=16.82, 95% CI=-22.85, -10.80) than fourth-grade boys. Fifth-grade girls reported significantly fewer minutes in SPA (MD=8.41, 95% CI=7.15, 9.67), OSTPA (MD=18.99, 95% CI=17.28, 20.70), and significantly more minutes in SB (MD=21.66, 95% CI=-26.92, -16.40) than fifth grade boys. High SES schools of fourth-grade students reported significantly fewer minutes in SB (MD=7.18, 95% CI=-14.42, 0.04) compared to low SES schools of fourth-grade students. CONCLUSION: There were no significant differences among rural and non-rural schools of fourth and fifth-grade students with respect to outside of school time physical activity and sedentary behavior. Rural schools of fifth-grade students reported more minutes in school physical activity. Gender differences were observed as girls reported significantly lower school physical activity, out of school physical activity, and significantly higher sedentary behavior than boys. Future studies need to more closely examine definitions of rural and non-rural environments, the physical activity domains under question, as well as, to examine of socioeconomic status.
Keywords: Rurality; Physical activity; Sedentary behavior; School; Gender